Factors facilitating pest infestation in two low-income urban areas of Cape Town, South Africa : an urban health observation study - Mngadi, Nontokozo (Department of Public Health and Family Medicine, 2016)
High pest burdens in low-income urban areas pose a significant public health threat to residents due to pest-induced diseases and other negative health consequences. Furthermore, pests can also be a source of nuisance and social stigma. To ward off pests and the problems they are associated with, many residents of socioeconomically disadvantaged urban areas frequently use pesticides, including highly toxic illegal pesticides. Inappropriate and indiscriminate use of pesticide is a concern since pesticide exposures can put residents, especially children, at risk for negative health effects. While pesticide use and exposures are common in many low socioeconomic urban areas globally, pesticide-induced adverse health effects are of particular concern in developing countries, such as South Africa, where pesticide regulations and enforcement thereof is often lacking. Following the alarming rise in number of children hospitalized with pesticide poisoning in the Cape Town surrounds, researchers at the University of Cape Town conducted a study whose aim was to identify common in-home pests, pesticide use and exposure patterns, and pesticide risk perceptions in Khayelitsha and Philippi, two low socioeconomic communities of Cape Town. This study was part of the larger project and was focused on investigating factors that contribute to pest infestation in low socioeconomic urban areas. An analysis of qualitative data that examined factors in housing, environment and practices and pest control behaviours of poor urban residents that facilitate pest infestation is presented in this mini-dissertation. The protocol (Part A) describes the study population and the methods used to collect and analyse the data. The structured literature review (Part B) describes the double health burden from pests and pesticide exposure faced by low-income urban residents. It also discusses the poverty-related factors that contribute to pest infestations in impoverished urban areas. Lastly, it critically evaluates research on alternative non-toxic pest control methods relevant for low socioeconomic urban communities.